Pengaruh Pemahaman Wajib Pajak, Sanksi Denda Pajak dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak UMKM di KPP Pratama Rungkut Surabaya - Fikih Fadillyna Pratiwi; Susanti Susanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
The purpose of this study is to determine the influence of understanding, fines and awareness of taxpayers on MSME taxpayer compliance. This type of research is quantitative research. The population in this study is MSMEs registered at KPP Pratama Rungkut Surabaya with the number of sample of 40 active taxpayers. method data collection using questionnaires and tests. Technique Analysis of the data used Multiple Linear Regression using IBM SPSS statistic 25 for windows program. The results show that the understanding, fines and awareness of taxpayers had a significant effect on MSME taxpayer compliance either simultaneously or partially.